The Influence of Ethics, Integrity, Auditor's Experience and Auditor's Motivation on Auditor's Professionalism - Hayati, Keumala; Ambarita, Agung Alanuari; Sebayang, Sherin Tharia Br; Sitompul, Micheel Hartasia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research was conducted to see the effect of ethics, integrity, and auditor experience and auditor motivation on auditor professionalism. This research was obtained directly through the accumulation of data, where this study used saturated sampling consisting of 65 samples. This study analyzes through a study method that is multiple linear regression, T test and F test. (X1) Auditor Ethics variable has a positive effect and Sig on Auditor Professionalism. (X2) Auditor Integrity variable has no effect and no Sig on Auditor Professionalism. (X3) Auditor Experience variable has no effect and no Sig on Auditor Professionalism. (X4) Auditor Motivation variable has a positive and sig effect on Auditor Professionalism. Simultaneously the influence of ethics, integrity, auditor experience and auditor motivation have a positive and significant effect on auditor professionalism.